Overview of autotoxicity in alfalfa (Medicago sativa L.): Identifying gaps between laboratory findings and demonstration at field scale - Paige Baisley; Kimberly A. Cassida (Grassland Research)
Abstract Autotoxicity is a type of intraspecific allelopathy in which compounds released by a plant inhibit the growth of other plants of the same species. In alfalfa (Medicago sativa L.), an herbaceous perennial legume widely used in hay and pasture production, autotoxicity is associated with re‐establishment failure, reduced yields, and decreased persistence. Several compounds in the phenolic and saponin groups are suspected to contribute to alfalfa autotoxicity, but the exact compounds, ratio of compounds, and concentration of compounds necessary for autotoxicity are not fully defined. Symptoms of autotoxicity, including decreased germination and inhibited root elongation, are consistently observed in laboratory bioassays, but evidence to consistently implicate autotoxicity in poor alfalfa growth at field scale is lacking. This review article presents three criteria that address the production and accumulation of autotoxic compounds in alfalfa and distinguish symptoms of autotoxicity from other inhibitory factors in the field. These criteria provide a useful framework to highlight both competencies and gaps in our current understanding of alfalfa autotoxicity.